2023
DOI: 10.3389/fendo.2023.1181452
|View full text |Cite
|
Sign up to set email alerts
|

Is increased myocardial triglyceride content associated with early changes in left ventricular function? A 1H-MRS and MRI strain study

Abstract: BackgroundType 2 diabetes (T2D) and obesity induce left ventricular (LV) dysfunction. The underlying pathophysiological mechanisms remain unclear, but myocardial triglyceride content (MTGC) could be involved.ObjectivesThis study aimed to determine which clinical and biological factors are associated with increased MTGC and to establish whether MTGC is associated with early changes in LV function.MethodsA retrospective study was conducted using five previous prospective cohorts, leading to 338 subjects studied,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…A comparison between patients with and without AF revealed that the AF group had 1.6-fold higher plasma triglycerides and increased inflammation markers [ 65 ]. Increased myocardial triglyceride content (MTGC), as measured by magnetic resonance spectroscopy, has been linked to diastolic dysfunction, although the precise connection between MTGC and plasma triglycerides remains unclear [ 66 ]. Recent studies have suggested a connection between postprandial, very low-density lipoprotein (VLDL), composed of triglycerides, and atrial remodeling in MetS patients [ 67 ].…”
Section: A Correlation Exists: But Why?mentioning
confidence: 99%
“…A comparison between patients with and without AF revealed that the AF group had 1.6-fold higher plasma triglycerides and increased inflammation markers [ 65 ]. Increased myocardial triglyceride content (MTGC), as measured by magnetic resonance spectroscopy, has been linked to diastolic dysfunction, although the precise connection between MTGC and plasma triglycerides remains unclear [ 66 ]. Recent studies have suggested a connection between postprandial, very low-density lipoprotein (VLDL), composed of triglycerides, and atrial remodeling in MetS patients [ 67 ].…”
Section: A Correlation Exists: But Why?mentioning
confidence: 99%